The Effect of Migration on Income Convergence: Meta-Analytic Evidence - Ceren Ozgen; Peter Nijkamp; Jacques Poot (Tinbergen Institute, 2009)
Using meta-analytical techniques, we focus on 11 studies that explicitly measure the effect of a net migration variable in neoclassical convergence models and derive 57 comparable effect sizes. The data suggest that an increase in the net migration rate of one percentage point increases on average the GDP per capita growth rate by 0.13 percent, thus suggesting a net migration impact that is more consistent with endogenous self-reinforcing growth rather than neoclassical convergence. However, studies that use panel models or IV estimation yield smaller coefficients of net migration while the opposite is the case for regressions controlling for high-skilled migration.
Keywords: O15; O18; R23; R11; 330; Internal migration; income convergence; meta-analysis; regional disparities; Binnenwanderung; Regionale Entwicklung; Entwicklungskonvergenz; Regionale Wachstumstheorie; Schätzung; Meta-Analyse; Welt